Exploring the life cycle management of industrial solid waste in the case of copper slag. Issue 6 (June 2013) - Song, Xiaolong; Yang, Jianxin; Lu, Bin; Li, Bo
Industrial solid waste has potential impacts on soil, water and air quality, as well as human health, during its whole life stages. A framework for the life cycle management of industrial solid waste, which integrates the source reduction process, is presented and applied to copper slag management. Three management scenarios of copper slag are developed: (i) production of cement after electric furnace treatment, (ii) production of cement after flotation, and (iii) source reduction before the recycling process. A life cycle assessment is carried out to estimate the environmental burdens of these three scenarios. Life cycle assessment results showed that the environmental burdens of the three scenarios are 2710.09, 2061.19 and 2145.02 Pt respectively. In consideration of the closed-loop recycling process, the environmental performance of the flotation approach excelled that of the electric furnace approach. Additionally, although flash smelting promotes the source reduction of copper slag compared with bath smelting, it did not reduce the overall environmental burdens resulting from the complete copper slag management process. Moreover, it led to the shifting of environmental burdens from ecosystem quality damage and resources depletion to human health damage. The case study shows that it is necessary to integrate the generation process into the whole life cycle of industrial solid waste, and to make an integrated assessment for quantifying the contribution of source reduction, rather than to simply follow the priority of source reduction and the hierarchy of waste management.